Strategic Investment and Market Integration - Mattias Ganslandt (The Research Institute of Industrial Economics (IUI), 2001)
The competitive effect of international market integration in industries with imperfect competition is of great policy interest. This paper focuses on the link between monopolization and market segmentation. It presents a model of multi-market entry deterrence with or without market commitments. We derive sufficient conditions for entry deterrence with productive capacity in the multi-market game. It is shown that to deter entry in the multi-market game, the first-mover installs productions capacity which is strictly larger than the capacity needed to deter entry, if it is possible to assign parts of the capacity to specific markets. Market integration for production capacity may, thus, have a pro-competitive effect in international markets.
Keywords: F12; F15; L12; 330; Entry Deterrence; Multi-Market Competition; Market Integration; Markteintritt; Marktintegration; Kapazitätsplanung; Theorie